Analysis on Behavior Factors of Successful Entrepreneurship of College Students of Local University in Guangdong Province - Li Bing-quan; Hu Rong; Du Hai-xin; Zhang Xu-dong (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
Research purpose: To understand the behavioral factors affecting the success of college students’ Entrepreneurship. Research tools: the College Students’ Daily Success Behavior Scale (CSDSB) and the College Students’ Entrepreneurship Scale (CSES). Research methods: Psychometric method and Interview method. Research objects or samples: 32 college students in Guangdong Province who are starting their own businesses. Results: (1) The total score of college students’ daily success behavior and its five dimensions are positively correlated with the total score of college students’ entrepreneurship and its four dimensions. (2) The total score of college students’ daily success behavior and the dimension of “Excelsior (Ex)” have significant positive predictive effects on their entrepreneurial ability (F = 32.375, P < 0.001). (3) Successful entrepreneurs possess behavioral quality consistent with the dimensions of the college students’ daily behavior scale. Conclusion: Daily behavioral factors have a significant positive predictive effect on college students’ entrepreneurship.